2016
DOI: 10.1007/s13205-016-0392-z
|View full text |Cite
|
Sign up to set email alerts
|

Confamiliar transferability of simple sequence repeat (SSR) markers from cotton (Gossypium hirsutum L.) and jute (Corchorus olitorius L.) to twenty two Malvaceous species

Abstract: Cross-species transferability is a quick and economic method to enrich SSR database, particularly for minor crops where little genomic information is available. However, transferability of SSR markers varies greatly between species, genera and families of plant species. We assessed confamiliar transferability of SSR markers from cotton (Gossypium hirsutum) and jute (Corchorus olitorius) to 22 species distributed in different taxonomic groups of Malvaceae. All the species selected were potential industrial crop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 20 publications
(30 reference statements)
1
22
0
Order By: Relevance
“…In flowering plant, the efficiency of cross-species transfer of SSR markers is highly variable among taxa, especially when important differences in genome complexity exist between the marker source and the target [64]. Nevertheless, this method has been used successfully for accelerating the analysis of genetic diversity in many plant species, including palms [13,6870] In the present study, we find that the transferability rate of microsatellite markers developed in other palms genera to the African fan palm, i.e. their ability to successfully amplify genomic DNA from the latter species, is very low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In flowering plant, the efficiency of cross-species transfer of SSR markers is highly variable among taxa, especially when important differences in genome complexity exist between the marker source and the target [64]. Nevertheless, this method has been used successfully for accelerating the analysis of genetic diversity in many plant species, including palms [13,6870] In the present study, we find that the transferability rate of microsatellite markers developed in other palms genera to the African fan palm, i.e. their ability to successfully amplify genomic DNA from the latter species, is very low.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, they are markers of choice for the assessment of polymorphism among species, genetic structure within populations, phylogeny reconstruction, genetic mapping, evolutionary analysis, and molecular breeding [1114]. However, the steps leading to the development of functional SSR markers, namely the initial identification of microsatellite loci, primer selection and assessment of amplification/polymorphism detection, require some prior knowledge of the genome of the target species and may prove to be expensive and time-consuming [13,15]. In order to overcome this difficulty, approaches relying on the transfer of SSR markers between species or genera have therefore been implemented.…”
Section: Introductionmentioning
confidence: 99%
“…Rest 17 primers were selected from other species of genus Acacia. Transferability of genomic resources from one species to another depends on upon the phylogenetic relationship between different species [48]. Genus Acacia is presently divided into three main subgenera: Acacia, Aculiferum and Phyllodinae (syn.…”
Section: Correlation Analysismentioning
confidence: 99%
“…Lack of high-quality genome sequences restricts usage of SSRs for the molecular characterization of both loose smut and Karnal bunt pathotypes. Previous studies have shown the SSR marker crosstransferability to closely related species and related genera (Peakall, Gilmore, Keys, Morgante, & Rafalski, 1998;Satya, Paswan, Ghosh, Majumdar, & Ali, 2016). Despite transfer rates of SSRs between genera of up to 10% in eudicots (Barbara et al 2007), a possible high transferability between distant genera has also been observed in some species (Gutierrez et al 2005;Rai et al 2013).…”
mentioning
confidence: 99%